Socioeconomic importance of the emergence of savings and credit groups in the cassava (Manihot esculenta crantz) value chain in Inharrime district, Inhambane province in Mozambique (Research, Society and Development, 2022)
Savings and credit groups have been seen as an option for financing low-income families, excluded by the formal financial system. This article aims to assess the socio-economic impact of the activities of savings and credit groups in the cassava value chain in Inharrime district, Inhambane Province in Mozambique. This is a research with a qualitative and quantitative approach and to obtain the data, a survey was applied to about 81 members participating in savings and credit activities involved in the cassava value chain. These data were analyzed using the SPSS statistical program. The results show that with the implementation of savings and credit groups there was an improvement in the quality of life of these populations, with emphasis on food, housing, education and health indicators. These data reveal a positive impact of savings and credit groups, results mostly achieved through the commercialization of processed cassava commonly known as tapioca flour.